2014
DOI: 10.1097/igc.0000000000000213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Access to and Treatment in Specialist Facilities on Survival From Epithelial Ovarian Cancer in Australian Women: A Data Linkage Study

Abstract: Distance of residence from GOS hospitals in Australia is an important determinant of access to GOS hospitals. Treatment in a public or private GOS hospital and having surgery were the strongest predictors of survival from epithelial ovarian cancer. Research is required into the barriers to referral of patients with ovarian cancer for care in GOS hospitals; low population density limits options for supply of GOS in rural areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 16 publications
(21 reference statements)
0
25
1
Order By: Relevance
“…Knowing how realistic the proxy measure is would be a benefit, as it may dramatically change the distances/travel times calculated. For example, Tracey et al 57 identified in their study that only 37% of the patients attended the nearest facility, so using this as the proxy would underestimate the distances travelled by patients.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing how realistic the proxy measure is would be a benefit, as it may dramatically change the distances/travel times calculated. For example, Tracey et al 57 identified in their study that only 37% of the patients attended the nearest facility, so using this as the proxy would underestimate the distances travelled by patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with diffuse large B-cell lymphoma (DLBCL) (British Columbia study) or with ovarian, rectal, or other cancers (Australian studies) were analyzed [7,[31][32][33].These studies demonstrated that patients with lymphomas living in small and medium urban areas had worse overall survival (OS) than that of patients living in large urban areas [7].…”
Section: Travel Burden and Patient Outcomementioning
confidence: 99%
“…Most patients diagnosed with OC, survival is theorized to be 100%, who are still alive after 5-years, are presumably living with the disease rather than living disease-free. 5 Our analysis demonstrated that the DFS was 18.3 months (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). The Surveillance, Epidemiology and End Results-SEER database from 1995 to 2007 with epithelial OC who were actively followed-up and age 20 years or older were included for analyzing OS in the United States (40.692 patients) and OS was 65%, 44%, and 36% at 2, 5, and 10 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…18,[22][23][24][25][26] We scrutinized the analyzing related to various prognostic factors for OC. In the present study younger women, those diagnosed before the age of 40, had significantly better survival after five years than women diagnosed at older ages (p< 0.05).…”
Section: Discussionmentioning
confidence: 99%